Developments in Polymer Degradation—7 1987
DOI: 10.1007/978-94-009-3425-2_2
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Degradation Mechanisms in Condensation Polymers

Abstract: SUMMARY Thermal degradation processes occurring in the most common conden (polyurethanes, polyureas, polyesters, polycarbonates, polyamides, polyethers, polysulphides, polysiloxanes, polyphosphazenes, etc.).The thermal fragmentation pathways that can 'be defined on the basis of the existing information for condensation polymers are summarised in Table 7 in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 155 publications
1
27
0
Order By: Relevance
“…The curves of total ion We have ascertained above that, in the presence current (TIC) obtained by DPMS closely resemble of an appropriate catalyst, the PC/PMMA system the DTG curves obtained by TG. 26 undergoes an exchange reaction at 230ЊC in the The TGA curves of unmixed PC and PMMA molten state, producing a polycarbonate with together with those of some equimolar blends obmethacrylate and methyl carbonate chain ends tained by solvent casting and mechanical mixing (Scheme 2). Above 300ЊC, the exchange reaction are reported in Figure 5a,b.…”
Section: Resultsmentioning
confidence: 99%
“…The curves of total ion We have ascertained above that, in the presence current (TIC) obtained by DPMS closely resemble of an appropriate catalyst, the PC/PMMA system the DTG curves obtained by TG. 26 undergoes an exchange reaction at 230ЊC in the The TGA curves of unmixed PC and PMMA molten state, producing a polycarbonate with together with those of some equimolar blends obmethacrylate and methyl carbonate chain ends tained by solvent casting and mechanical mixing (Scheme 2). Above 300ЊC, the exchange reaction are reported in Figure 5a,b.…”
Section: Resultsmentioning
confidence: 99%
“…The application of four ramping temperature of 3°C min À1 in a temperature range to 210°C could induce the scission of certain chemical functional groups, such as the covalent band C-O-C, which are known to be the weak point of ester functions. Montaudo and Puglisi [26] located the initial degradation temperatures of polyesters between 230°C and 300°C under inert atmosphere.…”
Section: Post-cross-linking Effects On Mechanical Propertiesmentioning
confidence: 99%
“…The detailed degradation mechanism of PEEK is not yet clear owing to the complexity of the pyrogram, although comprehensive reviews of the thermal degradation mechanism were reported previously. 17,18 In the present work, thermal degradation behaviour of PEEK was investigated using a multi-state (or stepwise) Py/GC/MS method by consecutively heating the sample at fixed temperature intervals to achieve narrow temperature (~100 °C) pyrolysis conditions. This method is effective for analyzing PEEK because it can discriminate between the pyrolysates resulting from different pyrolysis temperatures.…”
mentioning
confidence: 99%